Pengaruh Financial Distress, Rentabilitas, Pertumbuhan Perusahaan dan Opini Audit terhadap Pergantian Auditor - Hilmah Anggraini; Dea Annisa; Dila Angraini; Wiwit Irawati; Tri Utami (Universitas Pamulang, 2020)
This review intends to look at and decide the impact of financial distress, profitability, company growth and audit opinion. This exploration was directed on real estate and property listed on the Indonesia Stock Trade-in 2014-2018. The example in this review utilized the purposive testing technique. This kind of exploration is quantitative with quantitative expressive techniques, gotten 29 organizations that are utilized as examination tests with perceptions for 5 (five) a long time, so the complete perceptions are 145 fiscal summaries that have been reviewed and audited. The insightful strategy utilized is illustrative measurements, information quality test, and speculation testing with an importance level of 5%. In the aftereffects of this review, monetary trouble and friends development showed no impact on evaluator turnover, while profitability, audit opinion assessment showed an impact on auditor turnover. Keywords: financial distress, profitability, company growth, audit opinion, auditor turnover